KEEFEKTIFAN TEKNIK PERMAINAN THEMATIC DOMINOES DALAM PEMBELAJARAN KOSAKATA BAHASA JEPANG (Eksperimen Terhadap Siswa Kelas XI SMA Negeri 9 Pekanbaru) - Suci Senessia; Sri Wahyu Widiati; Arza Aibonotika (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of the research to know the level of mastery of Japanese vocabulary of students before and after aplied thematic dominoes game techniques. This research used quasi experimental research with pretest posttest control group design. The object of this research is 20 students of experimental class and 20 students of control class. Data collection was performed by giving test. The given test was 25 items. The writer applies two tests, they are pretest and posttest. Pretest is given before the students are taught by implementing thematic dominoes game techniques, and posttest is given after the students are taught with implementing thematic dominoes game techniques. On average pretest results obtained by the experimental class students was 45,4 and at posttest increased by 37 into 82,4. While, On average pretest results obtained by the control class students was 44,3 and at posttest increased by 15,3 into 59,6. So there is a significant impact with application of thematic dominoes game techniques on the learning Japanese vocabulary of elevanth grade students at SMA N 9 Pekanbaru. Thus, it can be concluded that thematic dominoes game techniques was effective in the on the learning Japanese vocabulary.Keywords: Thematic Dominoes, Japanese Vocabulary